Ankle osteoarthritis and its association with severe ankle injuries, ankle surgeries and health-related quality of life in recently retired professional male football and rugby players: a cross-sectional observational study. Issue 6 (21st June 2020) - Paget, Liam D. A.; Aoki, Haruhito; Kemp, Simon; Lambert, Mike; Readhead, Clint; Stokes, Keith A; Viljoen, Wayne; Reurink, Gustaaf; Tol, Johannes L; Kerkhoffs, Gino M M J; Gouttebarge, Vincent
Abstract : Objectives: To determine (1) the prevalence of ankle osteoarthritis (OA) among former professional football and rugby players, (2) assess the association between ankle injuries or ankle surgeries with ankle OA, and (3) compare the mental and physical quality of life (QoL) between former professional football and rugby players with and without OA. Methods: We conducted a questionnaire-based observational study with a cross-sectional design. Former professional football and rugby players were recruited by the Football Players Worldwide and the International Rugby Players. Information concerning ankle OA, sustained ankle injuries and ankle surgeries was gathered (medical record or most recent medical professional). Health-related QoL was assessed using the Patient-Reported Outcomes Measurement Information System (PROMIS) physical and mental health scores. Results: Overall, 553 former professional football (n=401) and rugby (n=152) players were enrolled in the study (response rate of 56%). Ankle OA prevalence among former professional football and rugby players was 9.2% and 4.6%, respectively. Football players were more likely to suffer from ankle OA following every ankle injury and/or surgery. Football and rugby players with ankle OA had similar PROMIS physical and mental health scores to the norm for the general population. Conclusion: Former professional football and rugby players had higher ankle OA prevalence than the general population (3.4%). Football players are more likely to suffer from ankle OA following every ankle injury and/or surgery. No clinically relevant difference was seen for physical or mental health-related QoL among football and rugby players. Preventive measures for ankle injuries are recommended.